Effect of green technology innovation on the upgrading of the manufacturing value chain: Evidence from China - Wang, Xiuting; Zhou, Jun; Maitlo, Qamaruddin (Frontiers in Environmental Science, 2022)
Green technology innovation is an important driving force for the upgrading of the manufacturing value chain. The purpose of this study is to explore the effect of green technology innovation on the upgrading of the manufacturing value chain under institutional environments. To this aim, the panel data of 28 provinces in China from 2010 to 2019 and panel threshold regression model are applied. Empirical results show that the effect of green technology innovation on the upgrading of the manufacturing value chain is nonlinear under institutional environments. The effect of formal and informal institutional environments on the relationship between green technology innovation and the upgrading of the manufacturing value chain is also different. The positive effect of green technology innovation on the upgrading of the manufacturing value chain is best when the level of formal institutional environment is high and informal institutional environment is moderate. In addition, when we divide the sample into three regions (Eastern, Central, Western), the effect of green technology innovation on the upgrading of the manufacturing value chain under institutional environments shows regional heterogeneity. Hence, with this calculated optimal interval of institutional environments, the government can adjust and improve institutional environments so as to provide the most favorable institutional conditions for green technology innovation to promote the upgrading of the manufacturing value chain. This research is helpful for the government to make rational decisions according to the situation.